2013
DOI: 10.1002/etc.2079
|View full text |Cite
|
Sign up to set email alerts
|

Bottom‐up nutrient and top‐down fish impacts on insect‐mediated mercury flux from aquatic ecosystems

Abstract: Abstract-Methyl mercury (MeHg) is one of the most hazardous contaminants in the environment, adversely affecting the health of wildlife and humans. Recent studies have demonstrated that aquatic insects biotransport MeHg and other contaminants to terrestrial consumers, but the factors that regulate the flux of MeHg out of aquatic ecosystems via emergent insects have not been studied. The authors used experimental mesocosms to test the hypothesis that insect emergence and the associated flux of MeHg from aquatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 48 publications
2
27
1
Order By: Relevance
“…Mercury in dragonfly adults has been quantified in recent studies of mercury transfer to aquatic and terrestrial food webs . Tsui et al found that dragonflies collected near a stream had a mean MeHg concentration of 180 ng g −1 , which is comparable in the present study to 231 ng g −1 ± 73.5 ng g −1 dry weight for mature adults and 236 ng g −1 ± 50.0 ng g −1 for emerging adults.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Mercury in dragonfly adults has been quantified in recent studies of mercury transfer to aquatic and terrestrial food webs . Tsui et al found that dragonflies collected near a stream had a mean MeHg concentration of 180 ng g −1 , which is comparable in the present study to 231 ng g −1 ± 73.5 ng g −1 dry weight for mature adults and 236 ng g −1 ± 50.0 ng g −1 for emerging adults.…”
Section: Discussionsupporting
confidence: 81%
“…This finding suggests that weight loss may have a disproportionate impact on Hg(II) concentrations relative to MeHg concentrations. Jones et al [21] specifically sampled recently emerged dragonflies and reported %MeHg to be 78.5 AE 4.8%, which supports our finding of a 2fold increase in Hg(II) concentrations in emerging dragonflies over naiads and mature adults. The reason for high Hg(II) concentrations in emerging adults relative to MeHg concentrations (low %MeHg) is unclear, but it is suggestive of effects of weight loss or a mercury transformation mechanism.…”
Section: Mercury Quantification In Life Stagessupporting
confidence: 89%
“…As ponds age, sediment infilling causes them to become more shallow, and through time they change from permanent with fish to semipermanent without fish and eventually to temporary without fish. Our research has shown that the presence or absence of fish regulates insect emergence and the associated MeHg flux . In permanent ponds with fish, the biomass of small taxa (e.g., chironomids and mosquitoes) and large taxa (e.g., dragonflies) that emerge may be relatively similar .…”
Section: Conceptual Model Of Insect‐mediated Flux Of Mehg From Small mentioning
confidence: 87%
“…Because pond permanence influences aquatic community structure, permanence also influences insect emergence [9,10] and the potential effects of emergent insects on the surrounding terrestrial environment [23][24][25]. Insect emergence differs with the class of pond [9,10].…”
Section: Animals Commonly Associated With Aquatic Food Webs In the Grmentioning
confidence: 99%
“…Based on Henderson et al. (), Jones, Chumchal, Drenner, Timmins, and Nowlin (), Tweedy et al. (), and Chumchal and Drenner () [Colour figure can be viewed at wileyonlinelibrary.com]…”
Section: Network Of Effectsmentioning
confidence: 99%